Muhammad Abi Zahra’s Method in The Variety of Qira`āt in Tafsīr Zahrah al-Tafāsīr - Moh. Abdul Kholiq Hasan (Jurnal Studi Al-Qur'an, 2022)
This research aims at investigating Abi Zahra’s method towards the variety of the Qira`āt. This research paper employs the analytic descriptive method by exploring and analyzing the variety of Qira`āt in the Zahrah al-Tafāsīr. The results showed that Abi Zahra’s interaction methods towards the variety of Qira`āt are: (1) When presenting the Qiraāt, he often does not attribute the Qira`āt to their owner except in a small proportion (2) the diligence to present the Qira`āt Mutawātirah (3) Combine the Qira`āt (4) clarifying and explaining the Qira`āt (5) and explaining the Qira`āt Syāżah. Among his goals was to pay attention to the recitations in his interpretation, first: his assertion that all the frequent the Qira`āt are from the Qur’an, and that the meanings of those Qira`āt are all intended in the Qur’an and evidence of its miracles. Second: Using the Qira`āt to derive jurisprudential rulings and determine the meaning of the verse, because the Qira`āt are closely related to the position of of interpretation and the difference in rulings.